Surface Patterning of Metal Zinc Electrode with an In-Region Zincophilic Interface for High-Rate and Long-Cycle-Life Zinc Metal Anode - Wang, Tian; Xi, Qiao; Yao, Kai; Liu, Yuhang; Fu, Hao; Kavarthapu, Venkata Siva; Lee, Jun Kyu; Tang, Shaocong; Fattakhova‑Rohlfing, Dina; Ai, Wei; Yu, Jae Su (Nano-Micro Letters, 2024)
The undesirable dendrite growth induced by non-planar zinc (Zn) deposition and low Coulombic efficiency resulting from severe side reactions have been long-standing challenges for metallic Zn anodes and substantially impede the practical application of rechargeable aqueous Zn metal batteries (ZMBs). Herein, we present a strategy for achieving a high-rate and long-cycle-life Zn metal anode by patterning Zn foil surfaces and endowing a Zn-Indium (Zn-In) interface in the microchannels. The accumulation of electrons in the microchannel and the zincophilicity of the Zn-In interface promote preferential heteroepitaxial Zn deposition in the microchannel region and enhance the tolerance of the electrode at high current densities. Meanwhile, electron aggregation accelerates the dissolution of non-(002) plane Zn atoms on the array surface, thereby directing the subsequent homoepitaxial Zn deposition on the array surface. Consequently, the planar dendrite-free Zn deposition and long-term cycling stability are achieved (5,050 h at 10.0 mA cm−2 and 27,000 cycles at 20.0 mA cm−2). Furthermore, a Zn/I2 full cell assembled by pairing with such an anode can maintain good stability for 3,500 cycles at 5.0 C, demonstrating the application potential of the as-prepared ZnIn anode for high-performance aqueous ZMBs. Highlights: 1 A stable Zn anode was obtained by patterning Zn foil surfaces and endowing a zincphilic interface in microchannels. 2 The accumulation of electrons in the microchannel and the zincphilic interface promoted preferential heteroepitaxial Zn deposition in the microchannel region and subsequent homoepitaxial Zn deposition on the array surface. 3 The Zn symmetrical cells could undergo repeated plating/stripping for more than 25,000 cycles at the current densities of 10 and 20 mA cm−2.